2001
DOI: 10.1097/00061198-200110000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Light on the Stability of Latanoprost and its Clinical Relevance

Abstract: Latanoprost exhibits thermal and solar instability and should ideally be stored below room temperature and in the dark. The importance of these storage conditions should be conveyed clearly to the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 4 publications
3
26
0
Order By: Relevance
“…Therefore, the actual therapeutic efficacy of thermally stressed and/or degraded PGAs remains to be determined. The current data correlate reasonably well with thermal degradation rates for latanoprost previously published by Morgan et al, 29 who reported that latanoprost was stable at 48C and 258C but measured T90s of 8.3 and 1.3 days when stored at 508C and 708C, respectively. Other studies have measured the remaining concentration of PGAs collected directly from glaucoma patients after patient-directed storage with varying results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, the actual therapeutic efficacy of thermally stressed and/or degraded PGAs remains to be determined. The current data correlate reasonably well with thermal degradation rates for latanoprost previously published by Morgan et al, 29 who reported that latanoprost was stable at 48C and 258C but measured T90s of 8.3 and 1.3 days when stored at 508C and 708C, respectively. Other studies have measured the remaining concentration of PGAs collected directly from glaucoma patients after patient-directed storage with varying results.…”
Section: Discussionsupporting
confidence: 90%
“…Several published studies have assessed the stability 28,29 or efficacy 30,31 of PGAs under conditions of thermal stress or patient storage, and one has compared the stability of patient-stored samples of latanoprost and travoprost. 32 However, to our knowledge, no published study exists comparing the thermal stability of all three PGAs when stored under identical controlled experimental conditions while also simulating normal use by patients.…”
Section: Introductionmentioning
confidence: 99%
“…The HPLC-UV has been used but was limited to quantify latanoprost at microgram level. Morgan et al is the first to measure 12.2 μg mL −1 of latanoprost (minimum concentration) using this method but gave no information about RT [15]. Sakai et al also used this method to analyze latanoprost but neither the lowest concentration measured nor RT has been reported [16].…”
Section: Methods Optimizationmentioning
confidence: 99%
“…These analytical techniques are: high-performance liquid chromatography (HPLC) equipped with radioactive detectors [8][9][10][11][12][13], diode array detector [14], and UV detector [15][16][17][18][19][20]. The HPLC-UV is the simplest method for the quantification of latanoprost [19] but has longer analysis time (≥3.3 min).…”
Section: Fig 1 Chemical Structure Of Latanoprostmentioning
confidence: 99%
“…The recommendation for refrigeration was made based on experimental finding in the laboratory. There was 10% degradation after extreme exposure to 50°C for 198 hours (Morgan et al, 2001). In clinical practice, it is safe to transport and store at room temperature without reducing the effectiveness of the drug (Novak and Evans, 2001;Varma et al, 2006).…”
Section: Topical Latanoprost 0005%mentioning
confidence: 97%